The Effects of Tooth Brushing on Whole Salivary Flow Rate in Older Adults - Affoo, R. H. (Biomed Res Int, 2018)
OBJECTIVES: (1) To determine whether manual (MTB), or electric, tooth brushing (ETB) modulates whole salivary flow rate in older adults who are free of systemic disease. (2) To determine the duration of the brushing-related modulation of salivary flow rate. (3) To compare salivary flow rate modulation associated with MTB and ETB. METHOD: Twenty-one adults aged 60 years and older participated in two experimental sessions during which they used a manual, or electric, toothbrush to brush their teeth, tongue, and palate. Whole salivary flow rates were determined using the draining method before, during, and after brushing. Differences in salivary flow rates across time periods, and between conditions, were examined using paired samples t-tests applying a Holm-Bonferroni sequential procedure (p(corr) < 0.0045). The relationship between tooth brushing and age with respect to maximum salivary flow rate increase was examined using Pearson's correlation coefficient (p < 0.05). RESULTS/CONCLUSION: Whole salivary flow rates increased during, and for up to 5 minutes following, tooth brushing in adults aged 60 years and older who were free of systemic disease. The salivary effects of MTB and ETB were not significantly different. A moderate, positive correlation was observed between tooth-brushing-related maximum salivary flow rate increase and age.